2021
DOI: 10.3390/foods10112843
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Mystery of the Sweetness of Baijiu by Sensory Evaluation, Compositional Analysis and Multivariate Data Analysis

Abstract: Sweetness is an important Baijiu quality marker, but there is limited research on it. In this study, the main contributors to Baijiu sweetness were identified by “sensomics” combined with “flavoromics”. A total of 43 volatile compounds (mostly esters) were found that appeared to contribute to Baijiu sweetness, through sensory-guided fractionation and compositional analysis. Correlation analysis between the volatile composition and perceived sweetness of 18 Baijiu samples with different sweet intensities identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Dimethyl trisulfide, ethyl hexanoate, ethyl acetate, 3-methylbutyl acetate, 1,1-diethoxyethane, ethyl butanoate, hexanal, ethyl 2-methylpropanoate, ethyl 3-methylbutanoate, ethyl lactate and ethyl pentanoate could also be significant according to their high OAVs (>10). Interestingly, recent studies have found that ethyl hexanoate, with the aroma of pineapple, also makes great contributions to the pungency and sweetness perception of Baijiu [ 35 , 39 ]. Compounds, including 1-octen-3-ol, ethyl 2-methylbutanoate, 2-methylpropanol, butanoic acid, acetic acid, pentanoic acid, 1-propanol, 1-butanol, guaiacol, phenylacetaldehyde, β -ionone, hexanoic acid, 3-methylbutanoic acid, 3-methylbutanol were other aroma contributors (OAVs > 1).…”
Section: Resultsmentioning
confidence: 99%
“…Dimethyl trisulfide, ethyl hexanoate, ethyl acetate, 3-methylbutyl acetate, 1,1-diethoxyethane, ethyl butanoate, hexanal, ethyl 2-methylpropanoate, ethyl 3-methylbutanoate, ethyl lactate and ethyl pentanoate could also be significant according to their high OAVs (>10). Interestingly, recent studies have found that ethyl hexanoate, with the aroma of pineapple, also makes great contributions to the pungency and sweetness perception of Baijiu [ 35 , 39 ]. Compounds, including 1-octen-3-ol, ethyl 2-methylbutanoate, 2-methylpropanol, butanoic acid, acetic acid, pentanoic acid, 1-propanol, 1-butanol, guaiacol, phenylacetaldehyde, β -ionone, hexanoic acid, 3-methylbutanoic acid, 3-methylbutanol were other aroma contributors (OAVs > 1).…”
Section: Resultsmentioning
confidence: 99%
“…The esters may act as sensory modulators by inhibiting the activation of certain receptors that perceive spiciness, resulting in a milder and less intense spicy sensation. Although the addition of LCFAEEs offers benefits like flavor improvement and reduced spiciness, it is important to acknowledge that it also results in a decrease in the intensity of aroma release in the oral cavity [ 11 , 25 , 27 , 54 , 59 , 60 , 61 ]. This can be attributed to the physical properties of the esters, which may impede the diffusion of aroma compounds and their interaction with receptors in the mouth.…”
Section: Resultsmentioning
confidence: 99%
“…Baijiu has always been characterized by its open and natural multi-strain mixed fermentation [ 6 ]. Daqu is used as a matrix to naturally inoculate environmental microorganisms, which is applied to the fermentation of Baijiu [ 7 ]. Although the sesame flavor of Baijiu is based on the application of a series of optimized pure strains, namely, Bran Qu, the mixture of Daqu and Bran Qu is used as a saccharifying starter in sesame flavor Baijiu; hence, the main microorganisms and their metabolic pathways in the fermentation process of sesame flavor Baijiu are clearer and easier to control.…”
Section: Introductionmentioning
confidence: 99%